Reconsidering the body genre: Rape-revenge and postfeminist softcore as biocultural phenomena - David Andrews (Alphaville: Journal of Film and Screen Media, 2014)
Body genres represent ideal candidates for biocultural theorisation due to their almost universal effects on audiences. However, not all body genres can be interpreted at the formal level through a direct application of biological ideas; some require an indirect approach that emphasises cultural information as much as biological information. The article pursues this thesis by applying an understanding of heterosexual rape drawn from evolutionary psychology to the motifs of sexual coercion that structure two body genres: rape-revenge and postfeminist softcore. The biocultural approach may be applied in a direct way to rape-revenge, which has often been deemed offensive despite its critiques of male sexual coercion. This direct analysis may then be used as the foundation for a more indirect analysis of postfeminist softcore, a genre that stylises rape to remain inoffensive to women but in the process sacrifices its ability to critique the male aggression predicted by feminists and evolutionists alike.